KONSEP INTEGRASI NILAI-NILAI KEISLAMAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Moh. Hifzul Muiz; Uus Ruswandi; Bambang Samsul Arifin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Indeed, Islamic religious education has a very important role in shaping the character and behavior of students. Because Islamic education has an important function (necessary function) to actualize Islamic values in changing attitudes and behavior of students' lives that are currently happening. If studied more deeply, it was found that Islamic religious education at all levels of education has not shown a significant success in terms of inculcating attitudes and behavior in building the morals and ethics of students. This becomes a big question mark, which must be analyzed as soon as the main cause of all this. Thus, this paper will examine how the concept of integrating Islamic values is appropriate in learning Islamic religious education.